Edible mushrooms as an alternative to animal proteins for having a more sustainable diet: a review - Kimia Haji Ali Pashaei; Kiyavash Irankhah; Zahra Namkhah; Seyyed Reza Sobhani (BMC, 2024)
Abstract Background High protein sources especially animal protein is being used widely in people's diet. Ensuring a healthy and sustainable diet should be a global priority. Compared to diets rich in animal products, plant-based diets are more sustainable because they have less environmental impact. Aim of this article is to review mushroom's sustainability. Main body Using meat analogues like mushrooms seems to be a good option because their taste and texture are alike meat and they are sustainable healthy foods as they are good environmental choice due to their less water and land footprint but they are not a cost-benefit food. Conclusion Mushroom is a good nutritional and environmental meat substitute as it has less water and land footprint but not as a cost-benefit meat alternative. Therefore, the governments should make policies to use mushroom as an economical meat alternative and a source of protein for all consumers.